Potential beneficial and/or adverse effects of Capsicum annuum L. (cv. Fiesta) at two stage of ripening in CD-1 mice. Issue 11 (2nd June 2020) - Morittu, Valeria Maria; Pero, Maria Elena; Musco, Nadia; Mastellone, Vincenzo; Tudisco, Raffaella; Provenzano, Eugenio; Britti, Domenico; Menichini, Francesco; Infascelli, Federico; Lombardi, Pietro
Abstract: Aim of the present study was to evaluate the potential beneficial and/or adverse effects of Capsicum annuum L. (cv. Fiesta) extracts at two stage of ripening (immature and mature), and at two dosages (low and high) by evaluation of biochemical profile and oxidative status in CD-1 mice. The extracts were daily administered to mice by oral gavage for 20 days. At the end of the trial, the animals were euthanatized and blood was collected. Evidence of liver damage (increase of AST, ALT and bilirubin) in the group receiving the higher dosage of immature peppers extract were observed. Even if no adverse effects were seen at the lower doses, also no signs of beneficial effects in term of health status, biochemical profile and oxidative status were detected. These results are in contrast with in vitro findings and raise doubts about the possible use of Capsicum annuum L. (cv. Fiesta) as a nutritional supplement. Graphical Abstract: